2018
DOI: 10.3389/fmicb.2018.01997
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics Reveal a Flagellar System, a Type VI Secretion System and Plant Growth-Promoting Gene Clusters Unique to the Endophytic Bacterium Kosakonia radicincitans

Abstract: The recent worldwide discovery of plant growth-promoting (PGP) Kosakonia radicincitans in a large variety of crop plants suggests that this species confers significant influence on plants, both in terms of yield increase and product quality improvement. We provide a comparative genome analysis which helps to unravel the genetic basis for K. radicincitans' motility, competitiveness and plant growth-promoting capacities. We discovered that K. radicincitans carries multiple copies of complex gene clusters, among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 65 publications
1
34
0
1
Order By: Relevance
“…Kosakonia radicincitans is a bacterium of the Gram-negative family Enterobacteriaceae with plant growth-promoting properties [37]. The species has been found to be a native endophyte of a large variety of crop plants around the world [38]. Type strain DSM 16656 was repeatedly inoculated into diverse plant species and proved capable of establishing biofilms on roots [39].…”
Section: Occurrence and Use Of Tailocins In Plant Growth-promoting Bamentioning
confidence: 99%
See 1 more Smart Citation
“…Kosakonia radicincitans is a bacterium of the Gram-negative family Enterobacteriaceae with plant growth-promoting properties [37]. The species has been found to be a native endophyte of a large variety of crop plants around the world [38]. Type strain DSM 16656 was repeatedly inoculated into diverse plant species and proved capable of establishing biofilms on roots [39].…”
Section: Occurrence and Use Of Tailocins In Plant Growth-promoting Bamentioning
confidence: 99%
“…Type strain DSM 16656 was repeatedly inoculated into diverse plant species and proved capable of establishing biofilms on roots [39]. Comparison of the genome of DSM 16656 to other fully sequenced genomes of K. radicincitans and closely related bacterial taxa revealed that all to date known members of K. radicincitans exhibit genomic features that are absent from other closely related bacterial species, such as a duplicated flagellar system and an additional type VI secretion system [38].…”
Section: Occurrence and Use Of Tailocins In Plant Growth-promoting Bamentioning
confidence: 99%
“…The first case of a human bloodstream infection with K. radicincitans was reported in a 61-year-old man with cholangiocarcinoma in Houston, TX, USA, in Dec. 2016 4 . Unfortunately, the authors of this report considered some common features of enteric bacteria to be virulence factors, and confused type IV secretion systems with type IV pili that are involved in several phenomena, not only pathogenicity 12 . Comparison of the cases from Austria and the USA showed that both patients had problems in the bile duct system.…”
Section: Discussionmentioning
confidence: 99%
“…Genome analyses divulged a number of orthologs to innate plant growthpromoting genes for facilitating sustained production, such as those encoding stimulation of seedling germination (amyAS) and growth promotion (nasD, glnA, and nirD; phoABPR, acpho, phnCDEFGHJKLMNP, pqqCDEF, and gcd; and kdpABCDE and trkADGH) by inducing NPK uptake (10)(11)(12)(13)(14), heat shock proteins (dnaJK, groEL, and clpP), cold shock proteins (cspACDE and csh), and trehalose biosynthesis (otsAB), involved in abiotic stress tolerance (10). Furthermore, some genes involved in biocontrol functions, for instance, production of hydrogen cyanide (hcnABC), cell wall-degrading enzyme (chiDE), and acetoin (alsS and gdh) (10,11,15,16), and heavy metal efflux-mediated proteins (arsB, czcD, and nikAB) for arsenic, cadmium, cobalt, zinc, and nickel were incorporated in the genome of BTL07. Functional annotation also detected genes related to IAA phytohormones (dhaS, bioA, patB, and aldA), a siderophore (entABCDES), and antioxidant enzymes (katEG, sodABC, and bsaA) in this genome; these genes are likely to be linked with plant growth promotion by both direct and indirect pathways (10,11).…”
mentioning
confidence: 99%
“…Furthermore, some genes involved in biocontrol functions, for instance, production of hydrogen cyanide (hcnABC), cell wall-degrading enzyme (chiDE), and acetoin (alsS and gdh) (10,11,15,16), and heavy metal efflux-mediated proteins (arsB, czcD, and nikAB) for arsenic, cadmium, cobalt, zinc, and nickel were incorporated in the genome of BTL07. Functional annotation also detected genes related to IAA phytohormones (dhaS, bioA, patB, and aldA), a siderophore (entABCDES), and antioxidant enzymes (katEG, sodABC, and bsaA) in this genome; these genes are likely to be linked with plant growth promotion by both direct and indirect pathways (10,11).…”
mentioning
confidence: 99%